Primary squamous cell carcinoma of renal parenchyma: A case report and literature review - Liang, Ke; Yuan, Yichu; Lv, Bodong; Ke, Zunjin (Frontiers in Oncology, 2023)
Rationale Primary renal parenchymal squamous cell carcinoma (SCC) is an extremely rare tumor that is difficult to diagnose by hematology and imaging studies and is often diagnosed later than other primary renal cancers. Diagnosis A 52-year-old male patient was found to have cysts in both kidneys for 1 week. No urgency and frequency of urination, no dysuria, no gross hematuria, and no significant changes in recent body weight were reported. Interventions The upper pole of the right kidney is a cystic and solid mass (8.3 cm * 8.2 cm * 8.1 cm), the cystic part has long T1 and long T2 signals, the solid part has mixed signals, and some parts have limited diffusion. There were nodular long T1 and short T2 calcification signals. An enhanced scan of the solid part showed uneven enhancement and continuous enhancement of the mass capsule. Cystic renal cancer was considered because of the multiple cysts in both kidneys. Surgical treatment was performed. Postoperative pathology revealed well-differentiated squamous cell carcinoma of the right kidney with cystic degeneration, 8.5 cm * 6 cm in size, infiltrating the renal parenchyma, and the cutting edge was negative. The pathological stage was pT2bN0M0. Outcome At the follow-up 5 months after the operation, no metastasis was found. Conclusion Renal SCC is rare and easily misdiagnosed and missed. Pathological diagnosis is still the gold standard for its diagnosis. However, with active surgical treatment, the short-term prognosis of the patient is good.